Thoracic, abdominal and musculoskeletal involvement in Erdheim-Chester disease: CT, MR and PET imaging findings. - Antunes, C (2014)
BACKGROUND: Erdheim-Chester disease (ECD) is a rare, non-Langerhans cell histiocytosis with characteristic radiological and histological features. This entity is defined by a mononuclear infiltrate consisting of lipid-laden, foamy histiocytes that stain positively for CD68 and negatively for CD1a. Osseous involvement is constant and characteristic. Extra-osseous lesions may affect the retroperitoneum, lungs, skin, heart, brain and orbits. METHODS: Both radiography and technetium-99m bone scintigraphy may reveal osteosclerosis of the long bones, which is a typical finding in ECD. For visceral involvement, computed tomography (CT) is most useful, while magnetic resonance (MR) imaging is more sensitive for cardiovascular lesions; 2-[fluorine-18] fluoro-2-deoxy-d-glucose (FDG) positron emission tomography (PET)/CT scanning is useful in assessing the extension of ECD lesions. RESULTS: The prognosis is extremely variable and is often worse when there is cardiovascular system involvement. Diagnosis is based on the combination of radiographic, CT, MR imaging and nuclear medicine features and a nearly pathognomonic immunohistochemical profile. CONCLUSION: The aims of this work are to perform a systematic review of Erdheim-Chester disease as seen on imaging of the chest, abdomen and musculoskeletal system and to discuss the diagnostic workup and differential diagnoses according to the imaging presentation. Teaching points • Bone involvement is usually present in patients, and the imaging findings are pathognomonic of ECD. • The circumferential periaortic infiltration may extend to its branches, sometimes becoming symptomatic. • Cardiac involvement-the pericardium, right atrium and auriculoventricular sulcus-worsens its prognosis. • Perirenal infiltration extending to the proximal ureter is highly suggestive of this disease.